2021
DOI: 10.1111/anae.15311
|View full text |Cite
|
Sign up to set email alerts
|

Regional anaesthesia quality indicators for adult patients undergoing non‐cardiac surgery: a systematic review

Abstract: Summary Improvement in healthcare delivery depends on the ability to measure outcomes that can direct changes in the system. An overview of quality indicators within the field of regional anaesthesia is lacking. This systematic review aims to synthesise available quality indicators, as per the Donabedian framework, and provide a concise overview of evidence‐based quality indicators within regional anaesthesia. A systematic literature search was conducted using the databases MEDLINE, Embase, CINAHL and Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Subsequent literature review demonstrated uptake of the COS in 60%–70% of trials by 200916 and over 80% by 2017,17 with a further review in 201918 showing sustained uptake at this level. Quality indicators in regional anesthesia have been evaluated and reviewed recently,19 20 with calls to create consensus on what defines success in regional anesthesia 21. To our knowledge, this is the first COS in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent literature review demonstrated uptake of the COS in 60%–70% of trials by 200916 and over 80% by 2017,17 with a further review in 201918 showing sustained uptake at this level. Quality indicators in regional anesthesia have been evaluated and reviewed recently,19 20 with calls to create consensus on what defines success in regional anesthesia 21. To our knowledge, this is the first COS in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, quality indicators should also produce reliable and valid results [ 39 ]. However, several systematic reviews found that most quality indicators used in routine perioperative care were based on low level or no scientific evidence [ 7 , 44 , 45 ▪ , 46 ▪▪ ]. Conversely, clinical indicators should be feasible and applicable for potential audiences [ 39 ], but evidence-based indicators validated for research purposes are not always practicable in routine care.…”
Section: Why Is It Difficult To Define ‘Suitable’ Quality Indicators ...mentioning
confidence: 99%
“…Professional societies and other organizations have practically developed and worked with perioperative quality indicators for a long time. Such empirical indicators often lack a robust basis of scientific evidence [ 7 , 44 , 45 ▪ , 46 ▪▪ ], but they are usually feasible in routine care. Several anesthesiologists’ societies have published perioperative quality indicator sets on the internet (for details and abbreviations, see Table 1 ).…”
Section: Examples Of Quality Indicator Sets Empirically Developed In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…To do this, we need sustained investment into high-quality studies that demonstrate the impact it has on outcomes beyond just acute pain. Both Hamilton et al and Johnston et al provide a succinct overview of appropriate metrics worthy of evaluation, as well as frameworks such as the Institute for Healthcare Improvement's triple aim [27] for thinking about how regional anaesthesia may improve healthcare in general [28,29]. Investigation into important long-term patient outcomes such as chronic postoperative pain and cancer recurrence must also continue as there is a sound mechanistic rationale for peri-operative management incorporating regional anaesthesia, even if the clinical evidence is as yet somewhat equivocal [30,31].…”
Section: It Goes Without Saying That Equipping All Anaesthetistsmentioning
confidence: 99%